Stereotactic and Robotic Minimally Invasive Thermal Ablation of Malignant Liver Tumors: A Systematic Review and Meta-Analysis - Tinguely, Pascale; Paolucci, Iwan; Ruiter, Simeon J. S.; Weber, Stefan; de Jong, Koert P.; Candinas, Daniel; Freedman, Jacob; Engstrand, Jennie (Frontiers in Oncology, 2021)
Background: Stereotactic navigation techniques aim to enhance treatment precision and safety in minimally invasive thermal ablation of liver tumours. We qualitatively reviewed and quantitatively summarised the available literature on procedural and clinical outcomes after stereotactic navigated ablation of malignant liver tumours. Methods: A systematic literature search was performed on procedural and clinical outcomes when using stereotactic or robotic navigation for laparoscopic or percutaneous thermal ablation. The online databases Medline, Embase and Cochrane Library were searched. Endpoints included targeting accuracy, procedural efficiency and treatment efficacy outcomes. Meta-analysis including subgroup analyses were performed. Results: Thirty-four studies (2 randomised controlled trials, 3 prospective cohort studies, 29 case series) were qualitatively analysed and 22 studies included for meta-analysis. Weighted average lateral targeting error was 3.7mm (CI 3.2,4.2), with all four comparative studies showing enhanced targeting accuracy compared to free-hand targeting. Weighted average overall complications, major complications and mortality were 11.4% (6.7, 16.1), 3.4% (2.1, 5.1) and 0.8% (0.5, 1.3). Pooled estimates of primary technique efficacy were 94% (89, 97) if assessed at 1 – 6 weeks and 90% (87, 93) if assessed at 6 – 12 weeks post ablation, with remaining between-study heterogeneity. Primary technique efficacy was significantly enhanced in stereotactic versus free-hand targeting, OR 1.9 (1.2, 3.2)(n = 6 studies). Conclusions: Advances in stereotactic navigation technologies allow highly precise and safe tumour targeting, leading to enhanced primary treatment efficacy. The use of varying definitions and terminology of safety and efficacy limit comparability among studies, highlighting the crucial need for further standardization of follow-up definitions.